Recent advances in surface regulation and engineering strategies of photoelectrodes toward enhanced photoelectrochemical water splitting - Tan, Runfa; Sivanantham, Arumugam; Jansi Rani, Balasubramanian; Jeong, Yoo Jae; Cho, In Sun (Coordination Chemistry Reviews, 2023)
Key parameters for efficient and stable photoelectrochemical (PEC) water splitting include light absorption, charge transport, surface reaction (charge transfer), and photocorrosion. Notably, the photoelectrode surface plays a crucial role during water oxidation and reduction reactions because it directly interacts with the reactants (electrolytes). Significantly, the surface properties of the photoelectrode strongly influence the charge dynamics, reaction kinetics, stability, and light-harvesting properties during the PEC operation. Consequently, various surface regulation/engineering strategies have been explored to improve the PEC performance, e.g., tuning the morphologies, defects, facets, and depositing passivation layers and cocatalysts. Recently, increased attention has been given to emerging surface-regulation strategies, which are promising strategies for improving PEC performance. This critical review summarizes the key roles of the surface, common surface-regulation strategies, and mechanisms for PEC performance enhancement. In addition, the review discusses emerging surface-regulation strategies from material and method points of view. Material-based strategies include depositing unique surface-modification layers such as single-atom catalysts, quantum dots, MXenes, plasmonic particles, metal–organic frameworks, and organic polymers. Method-based strategies include post-etching/activating the surface chemical composition, such as chemical, electrochemical, plasma etchings, photoirradiation, and post-thermal activations. Finally, the critical challenges and future trends/perspectives in the emerging surface-regulation strategies for PEC water splitting are also highlighted.
Keywords: Charge dynamics; Emerging surface modifier; Etching and activation; Photocorrosion; Reaction kinetics; Surface regulation and engineering